MECHANICAL WRIST JOINTS WITH ENHANCED RANGE OF MOTION AND RELATED DEVICES AND METHODS - SARALIEV DANIEL P; WILLIAMS MATTHEW R; BRISSON GABRIEL F (2022)
손목부 조인트, 예를 들면 수술 기구용 손목부 조인트가, 제1 디스크, 제1 디스크와 인접한 제2 디스크, 그리고 제1 디스크와 제2 디스크를 통하여 뻗어 있는 구동 힘줄을 포함할 수 있다. 제1 디스크와 제2 디스크는 서로 맞물리는 각각의 대향하는 조인트부를 포함할 수 있다. 제1 디스크와 제2 디스크는 상기 조인트부로부터 분리된 대향하는 하중 지지면을 더 포함할 수 있다. 상기 구동 힘줄은 제1 디스크와 제2 디스크 중의 적어도 하나에 힘을 작용시켜서 제1 디스크와 제2 디스크 사이의 상대 회전을 유발할 수 있다. 제1 디스크와 제2 디스크는 서로에 대해 약 +/- 45도보다 더 큰 최대 회전 운동 범위를 가질 수 있다. A wrist joint, such as for a surgical instrument, may include a first disc, a second disc adjacent the first disc, and a drive tendon that extends through the first disc and the second disc. The first disc and the second disc may include respective opposing joint features that intermesh with one another. The first disc and the second disc may further include opposing load bearing surfaces separate from the joint features. The drive tendon may exert a force on at least one of the first and second discs to cause relative rotation between the first and second discs. The first and second discs may have a maximum rotational range of motion greater than about +/- 45 degrees relative to each other.